Musik Indie Makassar: Makna, Proses Publikasi, dan Lokalitas - Haeruddin, Kurniawan (Emik, 2024)
Indie music, which is based on the “do it yourself spirit,” allows performers to create works freely without any demands. Indie music moves, develops and slowly creates its own flow. Indie music in its own way chooses to be outside the mainstream or does not follow market orientation. While there is a lot of related existing literatures, little (if any) has studied the locality of indie music. This article fills the gap This research with a qualitative approach was carried out in Makassar City. Those who participated in this research were 10 people, who varied based on the basis of age (between 20 and 38 years) and status (four musicians and six music listeners). Data was obtained from in-depth interviews and observations. The study indicates that indie music is a type of music that originates from a form of freedom of expression that is not tied to industry standards and is not market-oriented. Indie music is not a genre, indie is the principle of independence of a musician. Indie music is never synonymous with a certain music genre, indie music is free to choose its genre. Indie music not only contains value in terms of its lyrics, but also in terms of its musicality. There are three stages that indie musicians go through before their work is finally published, namely the pre-production, production and distribution stages. The locality of music creates uniqueness in the world of indie music. However, this locality is not just about creating a geographically identifiable voice, but also about celebrating local heritage, culture and experiences. Meanwhile, indie musicians not only create music, but also become part of a community that grows together. Collaboration on a local scale creates a sense of togetherness, strengthening deep bonds between musicians and their communities. Adaptive attitudes are a major force in the world of indie music and adaptive schema in indie music refers to an approach that allows flexibility and evolution in musical creativity